2013
DOI: 10.3109/14767058.2013.791275
|View full text |Cite
|
Sign up to set email alerts
|

Fetal magnetic resonance imaging and neurosonography in congenital neurological anomalies: supplementary diagnostic and postnatal prognostic value

Abstract: Both imaging modalities give a high-diagnostic performance with a good degree of agreement between them, when made by specialized staff. Fetal MRI is a valuable complementary tool to detailed neurosonography which allows an evaluation of the normal brain maturation from the second trimester. It also offers a higher diagnostic performance for some congenital abnormalities such as cortical development or acquired lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…Clear details regarding USS technique (transabdominal or transvaginal, views obtained) and equipment (manufacturer, transducer) were provided in 21 studies [1820, 22, 2426, 28, 3237, 39, 40, 42, 43, 47, 48, 50]. The remaining 13 studies [3, 21, 23, 27, 29–31, 38, 41, 4446, 49] provided minimal information or details were not given.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clear details regarding USS technique (transabdominal or transvaginal, views obtained) and equipment (manufacturer, transducer) were provided in 21 studies [1820, 22, 2426, 28, 3237, 39, 40, 42, 43, 47, 48, 50]. The remaining 13 studies [3, 21, 23, 27, 29–31, 38, 41, 4446, 49] provided minimal information or details were not given.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias due to conduct and interpretation of the index tests was low risk in 15/34 (44 %) [3, 18, 20, 21, 25, 28, 30, 32, 3537, 40, 42, 43, 47], high risk in 4/34 (12 %) [38, 4446] and unclear in 15/34 (44 %) [19, 2224, 26, 27, 29, 31, 33, 34, 39, 41, 4850]. Assessment of potential bias introduced by the reference standard was considered low risk in 19/34 (56 %) studies [3, 18, 19, 21, 22, 24, 28–31, 35, 36, 38, 40, 44, 4750], high risk in nine (26 %) [20, 27, 3234, 41, 43, 45, 46] and unclear in 6/34 (18 %) [23, 25, 26, 37, 39, 42], as there were a proportion of cases within the study that did not have a confirmed outcome or it was determined by clinical examination. Bias in the flow and timing as judged by timing between USS and iuMR imaging or due to methods used for analysis of findings was deemed low in 15/34 (42 %) [3, 18, 19, 23–25, 30, 32, 33, 35, 39, 46, 47, 49], high in 11/34 (32 %) [21, 26, 31, 34, 3642] and unclear in 9/34 (27 %) [20, 22, 272...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported a higher accuracy of MRI compared with ultrasonography for diagnosing CNS anomalies. Others have shown that additional anomalies diagnosed by MRI may lead to a change in counseling and/or management.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the most reliable predictor for the development of neurological damage in CMV‐infected fetuses is viral load. It is now accepted that ultrasound and fhMRI are complementary methods. The most common fh‐detected pathologies in CMV‐infected fetuses are T2‐weighted hyperintense signals in subcortical white matter and anatomical changes.…”
Section: Discussionmentioning
confidence: 99%